Alzheimer’s disease health literacy: a challenge for communication professionals - Nunes, Tatiana Filipa Gomes (2017)
Alzheimer disease seems to be one of the greatest issues in occidental societies. In this paper we will discuss the level of knowledge among undergraduate communication students in Portugal and how the results helped developing the actual Portuguese Alzheimer Association‘s communication program.